1994
DOI: 10.1177/106342669400200404
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Of Intensive Case Management For Homeless Adolescents

Abstract: This article describes the Seattle Homeless Adolescent Research Project (SHARP), a research demonstration program with a goal of implementing and evaluating an intensive mental health case management program for homeless adolescents. This new program, Project Passage, is based on nine primary components: (a) assessment, (b) planning, (c) linkage, (d) monitoring or tracking, (e) advocacy, (f) counseling or the therapeutic relationship, (g) treatment teams, (h) crisis service, and (i) flexible funds. Case load w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 15 publications
0
99
1
Order By: Relevance
“…On substance use, ICM intervention had a small effect on substance-and drug-use outcomes. Two studies found significantly (p < .05) lower composite scores for alcohol or recent alcohol and cocaine use across groups (Cox et al, 1998;Stahler et al, 1995); Other studies reported minimal improvements in problematic substance use or no significant between-group differences in measures of alcohol or drug use (Burnam, 1995;Cauce, 1994;Malte et al, 2017;Orwin et al, 1994;Stahler et al, 1995;Toro et al, 1997). In three trials, ICM interventions resulted in reductions in hospitalisations and health-care utilisation (Marshall et al, 1995;Rosenblum et al, 2002;Shumway et al, 2008).…”
Section: Intensive Case Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…On substance use, ICM intervention had a small effect on substance-and drug-use outcomes. Two studies found significantly (p < .05) lower composite scores for alcohol or recent alcohol and cocaine use across groups (Cox et al, 1998;Stahler et al, 1995); Other studies reported minimal improvements in problematic substance use or no significant between-group differences in measures of alcohol or drug use (Burnam, 1995;Cauce, 1994;Malte et al, 2017;Orwin et al, 1994;Stahler et al, 1995;Toro et al, 1997). In three trials, ICM interventions resulted in reductions in hospitalisations and health-care utilisation (Marshall et al, 1995;Rosenblum et al, 2002;Shumway et al, 2008).…”
Section: Intensive Case Managementmentioning
confidence: 99%
“…We included 16 studies (17 publications) examining the effectiveness of ICM (Braucht, 1995;Burnam, 1995;Cauce, 1994;Clark & Rich, 2003;Cox et al, 1998;Felton et al, 1995;Grace & Gill, 2014;Korr & Joseph, 1996;Malte et al, 2017;Marshall et al, 1995; Orwin…”
Section: Intensive Case Managementmentioning
confidence: 99%
“…Addressing these needs effectively can be challenging, given the growing autonomy (and thus, distinct agendas) of youth, conflict in parent-youth relationships, and the increased complexity of youths’ family and social networks as they get older. In addressing situations in which parent-youth relationships suffer from high levels of conflict or are disengaged, but are still amenable to supportive intervention, it may be possible to use specialized family treatment strategies (e.g., Ecological Family Therapy & Family Focused Therapy; Slesnick & Prestopnik, 2009), more broadly based family preservation services (Kinney, Haapala, Madsen, & Fleming, 1991), or intensive case management (Wagner et al, 1994). In addition to directly addressing problems in parent-youth relationships preceding or exacerbated by homelessness, these strategies may help to prevent episodes of homelessness among youth or expedite reunification of parents with their children once a more permanent living arrangement is obtained.…”
Section: Recommendations: Addressing the Needs Of Children And Famili...mentioning
confidence: 99%
“…Quality of life was chosen as the primary outcome measure, as it is an important indicator of homeless young adult’s experience of their life (Bender et al, 2007; Johnson, Whitbeck, & Hoyt, 2005; Thompson, Pollio, Eyrich, Bradbury, & North, 2004). Furthermore, the few available effect studies among homeless young people (Ferguson & Xie, 2008; Wagner et al, 1994) and those among homeless people, including homeless youth (Bearsley & Cummins, 1999; Hubley, Russell, Palepu, & Hwang, 2014), showed improvement in the quality of life after receiving care. Also, it was found that quality of life was associated with different positive outcomes such as psychological well-being and independent housing (Hubley et al, 2014; Thompson et al, 2004; J.…”
Section: Introductionmentioning
confidence: 99%